A Roadmap for Research Culture and Digital Transformation in Indonesian Student Organizations: a Case of PP HIMA PERSIS (2025–2028) - Fadhlurrohman, Hafidh; Sawalludin, Faizal Rizqi; Surizkika, Aldi (Universitas Pahlawan Tuanku Tambusai, 2026)
This article offers a roadmap for revitalizing research culture and digital transformation for PP HIMA PERSIS for the 2025–2028 period, emphasizing that the main challenge is not merely a lack of individual skills or platforms, but rather the weak institutionalization of knowledge practices. Based on organizational learning theory and institutional perspectives, research is understood as an organizational capability that requires stable routines, output standards, quality assurance mechanisms, and documented organizational memory so that knowledge is cumulative and can be audited across management generations. Digital transformation in this framework is positioned as a governance infrastructure—repositories, revision trails, decision documentation, and workflow standardization—that enables organizations to